Prevalensi Infeksi Cacing Ancylostoma Spp Pada Kucing Lokal (Felis catus) Di Kota Denpasar - Oktaviana, Putu Anna; Dwinata, Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2014)
A long time ago local cat ( Felis catus ) is a symbol of faith and now it turns to mice controller or even pet. The efficiency of maintains and food make more people interested to take care of cat. Based on the area of living, cat can be categorized into three such as: (1) Domestic pet cats , (2) Stray cats  and (3) Feral cats . Domestic pet cats can be categorized into three also based on authority area such as  Indoor, Limited range and Free range. Cat disease can cause by parasite, virus, bacteria and fungus. There are some species of parasite which often be found in cat digest track such as Ancylostoma spp ,  Toxocara spp and Strongyloides spp. The purpose of this research is to know the prevalence of Ancylostomma spp . infection in local cat. This research use 80 samples which divide into 40 stray cat feces and 40 home cat feces using floatation method. From 40 samples of examinated stray cat feces, 19 samples (47.5%) positively found the egg of Ancylostoma spp . Meanwhile from 40 samples of examinated home cat feces, 10 samples  (25.0 %)  positively found the egg of Ancylostoma spp. After analyzed by Chi-square test, there is a clear relation between the prevalence of Ancylostoma spp. infection in home cat and stray cat. (P<0,05)
Keywords: Cat, Prevalence, Ancylostoma